Grass Cell Walls: A Story of Cross-Linking - Hatfield, Ronald D.; Rancour, David M.; Marita, Jane M. (Frontiers in Plant Science, 2017)
Cell wall matrices are complex composites mainly of polysaccharides, phenolics (monomers and polymers), and protein. We are beginning to understand the synthesis of these major wall components individually, but still have a poor understanding of how cell walls are assembled into complex matrices. Valuable insight has been gained by examining intact components to understand the individual elements that make up plant cell walls. Grasses are a prominent group within the plant kingdom, not only for their important roles in global agriculture, but also for the complexity of their cell walls. Ferulate incorporation into grass cell wall matrices (C3 and C4 types) leads to a cross-linked matrix that plays a prominent role in the structure and utilization of grass biomass compared to dicot species. Incorporation of p-coumarates as part of the lignin structure also adds to the complexity of grass cell walls. Feruoylation results in a wall with individual hemicellulosic polysaccharides (arabinoxylans) covalently linked to each other and to lignin. Evidence strongly suggests that ferulates not only cross-link arabinoxylans, but may be important factors in lignification of the cell wall. Therefore, the distribution of ferulates on arabinoxylans could provide a means of structuring regions of the matrix with the incorporation of lignin and have a significant impact upon localized cell wall organization. The role of other phenolics in cell wall formation such as p-coumarates (which can have concentrations higher than ferulates) remains unknown. It is possible that p-coumarates assist in the formation of lignin, especially syringyl rich lignin. The uniqueness of the grass cell wall compared to dicot sepcies may not be so much in the gross composition of the wall, but how the distinctive individual components are organized into a functional wall matrix. These features are discussed and working models are provided to illustrate how changing the organization of feruoylation and p-coumaroylation could lead to differing cell wall properties.